Photosynthetic efficiency and symbiont cover of Amphistegina lobifera measured by PAM fluorometry and CLSM during a menthol-DCMU bleaching experiment (Nov–Dec 2022, Bremen, Germany) - Diana N Puerto Rueda; Marleen Stuhr; Maoz Fine; Christiane Schmidt (PANGAEA, 2025)
This dataset contains experimental data from a one-month aquarium-based bleaching experiment conducted on Large Benthic Foraminifera (Amphistegina lobifera) from 16 November to 16 December 2022 at the Marine Experimental Facility of the Leibniz Centre for Tropical Marine Research (ZMT), Bremen, Germany. The aim of the experiment was to obtain symbiont-free A. lobifera individuals for future re-inoculation studies and symbiont switching experiments. The foraminifera were originally collected in May 2022 at the Interuniversity Institute for Marine Sciences (IUI) in Eilat, Israel (29°30 extquotesingle07.8N, 34°55 extquotesingle04.9E) and maintained in culture in Germany until the start of the experiment. To assess the effectiveness of two chemical agents—menthol and 3-(3,4-dichlorophenyl)-1,1-dimethylurea (DCMU)—in disrupting symbiosis, photosynthetic efficiency (measured as maximum quantum yield, Fv/Fm) was recorded every other day during the first week of the experiment using a Pulse-Amplitude-Modulated (PAM) fluorometer. Fv/Fm measurements were discontinued after the first week due to complete inhibition of photosynthesis. Symbiont coverage (%) was assessed on day one and then weekly until week four using Confocal Laser Scanning Microscopy (CLSM).